Workflow management models, methods, and systems - Aalst, Wil van der (MIT Press, 2002)
This book offers a comprehensive introduction to workflow management, the management of business processes with information technology. By defining, analyzing, and redesigning an organization's resources and operations, workflow management systems ensure that the right information reaches the right person or computer application at the right time. The book provides a basic overview of workflow terminology and organization, as well as detailed coverage of workflow modeling with Petri nets. Because Petri nets make definitions easier to understand for nonexperts, they facilitate communication between designers and users. The book includes a chapter of case studies, review exercises, and a glossary. A special Web site developed by the authors, www.workflowcourse.com, features animation, interactive examples, lecture materials, exercises and solutions, relevant links, and other valuable resources for the classroom.
Originally published under the title: Workflow management : modellen, methoden en systemen, 1997, by Academic Service.